Protective Effect of Free and Bound Polyphenol Extracts from Ginger (Zingiber officinale Roscoe) on the Hepatic Antioxidant and Some Carbohydrate Metabolizing Enzymes of Streptozotocin-Induced Diabetic Rats. (3rd December 2013) - Kazeem, Mutiu Idowu; Akanji, Musbau Adewunmi; Yakubu, Musa Toyin; Ashafa, Anofi Omotayo Tom
Abstract : This study investigated the hepatoprotective effects of polyphenols from Zingiber officinale on streptozotocin-induced diabetic rats by assessing liver antioxidant enzymes, carbohydrate-metabolizing enzymes and liver function indices. Initial oral glucose tolerance test was conducted using 125 mg/kg, 250 mg/kg, and 500 mg/kg body weight of both free and bound polyphenols from Z. officinale . 28 day daily oral administration of 500 mg/kg body weight of free and bound polyphenols from Z. officinale to streptozotocin-induced (50 mg/kg) diabetic rats significantly reduced (P < 0.05 ) the fasting blood glucose compared to control groups. There was significant increase (P < 0.05 ) in the antioxidant enzymes activities in the animals treated with both polyphenols. Similarly, the polyphenols normalised the activities of some carbohydrate metabolic enzymes (hexokinase and phosphofructokinase) in the liver of the rats treated with it and significantly reduced (P < 0.05 ) the activities of liver function enzymes. The results from the present study have shown that both free and bound polyphenols from Z. officinale especially the free polyphenol could ameliorate liver disorders caused by diabetes mellitus in rats. This further validates the use of this species as medicinal herb and spice by the larger population of Nigerians.